x+3+1-9x=

Simple and best practice solution for x+3+1-9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3+1-9x= equation:


Simplifying
x + 3 + 1 + -9x = 0

Reorder the terms:
3 + 1 + x + -9x = 0

Combine like terms: 3 + 1 = 4
4 + x + -9x = 0

Combine like terms: x + -9x = -8x
4 + -8x = 0

Solving
4 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -8x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -8x = 0 + -4
-8x = 0 + -4

Combine like terms: 0 + -4 = -4
-8x = -4

Divide each side by '-8'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -17+x=x+22 | | G=3F+24 | | 3/8+x=5x | | 70=-3x | | p=9+1+s | | 16/8(2)x6 | | 1/3x+11+x=2-9x+14 | | 5x-2(x+4)=9 | | -4(6-7v)-2(1-5v)=12 | | -8x-77=170+5x | | 8n-3n+3= | | 4a+7a+6=0 | | 2y+2x+16=60 | | 5a+8+(-2a)=7 | | 8-(3*-2)-2= | | 121.824=-7.52(1+4k) | | 251/500=x | | -2*(x-3)=18 | | 50-9x=18+7x | | 91/2/2 | | 1/9(9x-4)=(x-4)/(18) | | m+n=20 | | 4(5b-3)= | | 4-6k-5k= | | -2*-9-3*-3+1= | | 11c-88=(-22)-8c | | X/2=16.5 | | 4x^2+3y=36 | | 3x+22/7+x+11/5=11 | | 54/5x=-521/5 | | 17=9+2x | | 3x^2y^-3/12x^6y^3 |

Equations solver categories